2018
DOI: 10.3390/ijerph15112479
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Modulation of Saliva Microbial Composition and Cytokine Levels

Abstract: Tobacco use has been implicated as an immunomodulator in the oral cavity and contributes to the development of oral cancer. In the present study, we investigated the effects of cigarette smoking on bacterial diversity and host responses compared to healthy nonsmoking controls. Saliva samples were collected from eighteen smokers and sixteen nonsmoking individuals by passive drool. The 16S rRNA gene was used to characterize the salivary microbiome by using the Illumina MiSeq platform. Cytokine and chemokine expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 101 publications
4
38
1
Order By: Relevance
“…Our analysis revealed that smoking reduced the salivary microbial diversity and Bacteroidetes was the most abundant phylum observed, which has been reported previously [31]. Moreover, the genus Prevotella was more abundant in the smokers compared to non-smokers, suggesting therefore an increased vulnerability of the smokers to develop oral diseases such as gingivitis [31]. This suggests that smoking has to always be considered in the future when assessing the oral microbiome composition, as it clearly affects the salivary microbiome composition.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our analysis revealed that smoking reduced the salivary microbial diversity and Bacteroidetes was the most abundant phylum observed, which has been reported previously [31]. Moreover, the genus Prevotella was more abundant in the smokers compared to non-smokers, suggesting therefore an increased vulnerability of the smokers to develop oral diseases such as gingivitis [31]. This suggests that smoking has to always be considered in the future when assessing the oral microbiome composition, as it clearly affects the salivary microbiome composition.…”
Section: Discussionsupporting
confidence: 79%
“…Prior studies had shown that smoking disrupts the microbial homeostasis leading to various oral disease such as gingivitis and dental loss [72]. Our analysis revealed that smoking reduced the salivary microbial diversity and Bacteroidetes was the most abundant phylum observed, which has been reported previously [31]. Moreover, the genus Prevotella was more abundant in the smokers compared to non-smokers, suggesting therefore an increased vulnerability of the smokers to develop oral diseases such as gingivitis [31].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Previous studies showed associations of increased risk for oral cancer with TNF-β polymorphisms genes and increased expression of salivary IL-4 and IL-13 [72,95]. Other studies comparing salivary cytokines of clinical samples and controls found increased expression of IL-2 and IL-4 in smokers and in patients with oral lichen planus (a chronic inflammatory disease that affects the oral mucosa) [96,97]. Besides, increased salivary IL-4 also has been associated with periodontitis [97][98][99].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies comparing salivary cytokines of clinical samples and controls found increased expression of IL-2 and IL-4 in smokers and in patients with oral lichen planus (a chronic inflammatory disease that affects the oral mucosa) [96,97]. Besides, increased salivary IL-4 also has been associated with periodontitis [97][98][99]. However, data about such salivary cytokines (TNF-β, IL-2, IL-4, and IL-13) in alcohol users were not found.…”
Section: Discussionmentioning
confidence: 99%